Pulsed electron beam facility GESA-SOFIE for in-situ characterization of cathode plasma dynamics. (November 2017) - Fetzer, Renate; An, Wladimir; Weisenburger, Alfons; Mueller, Georg
Abstract: A new pulsed electron beam facility was constructed, which is specially designed to investigate the cathode plasma on the microsecond timescale. The new triode type accelerator GESA-SOFIE is equipped with a large-area explosive emission cathode. The electron beam is focused on the target in a guiding magnetic field. Particle-in-cell code simulations were used to develop an enhanced and more flexible design compared with the previous facilities GESA I and GESA II. This concerned an improved adjustment of static electric field and magnetic field configurations, the possibility to tune shape and position of the electrodes, and an easy access for diagnostic tools to monitor the areas critical for operation. The performance of GESA-SOFIE was demonstrated for various operating conditions and the facility's versatile capabilities were shown. Typical values of GESA-SOFIE operation are electron energy 30-100 keV, beam current 50-180 A, beam cross-section 10-20 cm 2, and pulse duration up to 200 μs. Highlights: New pulsed electron beam facility GESA-SOFIE was designed and constructed. Typical beam parameters are 30–100 keV, 50-180 A, 10-20 cm 2  at target, 40-200 μs. GESA-SOFIE is specially designed to investigate the cathode plasma dynamics. Versatile static E and B field configurations and capabilities were demonstrated.